Racial disparities in breast cancer hereditary risk assessment referrals. Issue 4 (20th March 2020) - Peterson, Jennifer M.; Pepin, Abigail; Thomas, Rehema; Biagi, Tara; Stark, Elizabeth; Sparks, Andrew D.; Johnson, Kerry; Kaltman, Rebecca
Abstract: For poorly understood reasons, Black non‐Hispanic (BNH) women meeting National Comprehensive Cancer Network (NCCN) criteria for genetic testing for breast cancer risk are less likely than White non‐Hispanic (WNH) women to undergo testing (Armstrong, Micco, Carney, Stopfer, & Putt, JAMA, 293, 1729 and 2005). We compared physician referral rates and uptake for genetic testing of BNH and WNH women meeting select NCCN criteria (breast cancer under age 50, two primary breast cancers, triple‐negative disease under age 60) in the Cancer Center at George Washington University (GWCC) between 2015 and 2018. Of the 723 BNH and WNH patients treated for breast cancer at GWCC, 28% met study criteria for genetic counseling referral ( n  = 252; BNH n  = 115, WNH n  = 137). Physician referral rates to genetic counseling differed significantly by race (BNH 75.7%, n  = 87 and WNH 92.7%; n  = 127; χ 2  = 14.19, p ‐value < .01). Once referred, though, there was no significant difference in uptake of genetic counseling by race (BNH 95.4%, n  = 83; WNH 97.6%, n  = 124, χ 2  = 1.33, p ‐value = .25) for patients appropriately referred.